IDEOLOGI YANG BIAS GENDER DALAM NOVEL DUA PEREMPUAN KARYA APRILIA WAYAR - Awom, Iriano Yedija Petrus (Universitas Papua, 2018)
The aim of this study is to depict ideologies which consist of gender bias in the novel Ã¢Â€ÂœDua PerempuanÃ¢Â€Â (Two Women) by Aprilia Wayar as a form of patriarchy hegemony. The data of the observation is conversation or sentence in the novel which portrays gender bias mainly through the character and characterization of figures in the novel. This research uses descriptive analysis method by following steps like: identification, description, analysis, and summary as the finding. This finding indicates that the figures in the novel have been the subject of the hegemony through ideologies developed in society such as: patriarchy ideology, familial-ism ideology, motherhood ideology, and common ideology. Conscious and unconsciously these ideologies bring impact for gender bias like marginalization, stereotyping, violence, and double burden task to happen.